Involvement of multiple aluminium exclusion mechanisms in aluminium tolerance in wheat - Pellet, D; Papernik, L; Jones, D; Darrah, P; Grunes, D; Kochian, L (1997)
The goal of this study was to determine if Al-chelators other than malate are released from root apices and are involved in Al-tolerance in different wheat (Triticum aestivum L.) genotypes. Also we wanted to establish if root exudates contribute to increases in rhizosphere pH around the root tip. In seedlings of Al-tolerant Atlas, we have documented a constitutive phosphate exudation from the root apex. Because phosphate can complex Al and bind protons, it could play an important role in Al tolerance, both via complexation of Al3+ and by contributing to the alkalinization of rhizosphere pH observed at the apex of Atlas. This study suggests that in wheat, Al-tolerance can be mediated by multiple exclusion mechanisms controlled by different genes.